Business Competitiveness of Small Medium Enterprise in Pandemic Era Covid-19 (Case Study on Souvenir Business in the Special Economic Area of Tourism Likupang, North Sulawesi Province, Indonesia) - Arie Frits Kawulur; Noula Mawitjere; Hisky Kawulur (AIBPM Publisher, 2021)
This study aims to describe the small medium enterprises that grow and exist in